2020
DOI: 10.1111/obes.12364
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Smile Curves in Global Value Chains

Abstract: The logic of the ‘smile curve’ in the context of global value chains (GVCs) has been widely used in case studies of individual firms, but rarely identified at the country‐industry level by using real data. This paper puts forward a proposal, based on an inter‐country input–output model, to consistently measure both the gain of value added and the position of countries and industries when they join GVCs. This allows for better identification and mapping of economy‐wide smile curves in a given conceptual value c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(38 citation statements)
references
References 42 publications
1
35
0
2
Order By: Relevance
“…Hence, improving the country's position in the value chain is beneficial for not only wages but also labour demand. Such an improvement could be achieved via successful innovation (Meng et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, improving the country's position in the value chain is beneficial for not only wages but also labour demand. Such an improvement could be achieved via successful innovation (Meng et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…1-126), the founder of Acer, who observed that both ends of the value chain (pre-and post-production service activities) generate higher values added to the product than the middle of the value chain (fabrication activities). The smile curve logic has been widely used in the context of GVCs (Meng & Wei, 2020, pp. 988-1016.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This policy emphasis is based on the premise that a country can reap gains by joining global value chains on the basis of existing comparative advantages (for example, through the export of labour-intensive products) and then moving towards more sophisticated production processes. This concept is known as the smiling curve (Meng et al 2020;Mudambi 2008). Current import substitution proponents also promote high domestic value-added by upgrading towards high-value segments of the value chain.…”
Section: Value-added Ratiomentioning
confidence: 99%